2012
DOI: 10.1002/ajim.22086
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of exposure to occupational noise and mixed organic solvents on blood pressure in car manufacturing company workers

Abstract: Our results indicate that exposure to noise or a mixture of organic solvents may be associated with the prevalence of hypertension in car manufacturing company workers and co-exposure to noise and a mixture of solvents has an additive effect in this regard. Therefore appropriate preventive programs in these workers recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…times greater prevalence of CVD, such as hypertension (130). Other findings strongly support the theory that noise exposure has an impact on hypertension, and some data suggest that hearing loss and hypertension severity is associated (131)(132)(133). As such, this cross-sectional data supports the need for further evaluation of noise and CVD.…”
Section: Example 23supporting
confidence: 69%
“…times greater prevalence of CVD, such as hypertension (130). Other findings strongly support the theory that noise exposure has an impact on hypertension, and some data suggest that hearing loss and hypertension severity is associated (131)(132)(133). As such, this cross-sectional data supports the need for further evaluation of noise and CVD.…”
Section: Example 23supporting
confidence: 69%
“…Several prior studies have observed higher blood pressures among solvent-exposed workers than control groups across a variety of industries, including manufacturing and construction. 4,5,30–33 While not specifically assessed within this study, exposure durations and intensities appear to be important factors with longer durations and higher levels of exposure commensurate with higher systolic blood pressures reported in the literature. 5,30,33 Positive associations of solvent exposures with diastolic blood pressures have also been observed, although this relationship is less consistent than that of systolic blood pressures.…”
Section: Discussionmentioning
confidence: 87%
“…For example, employees at a car manufacturing plant exposed to mixed organic solvents were found to have an increased prevalence of hypertension compared with office workers at the same plant. 4 Other studies have observed associations of occupational exposure to solvents, metals, and pesticides in relation to insulin resistance and type 2 diabetes. 11,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies researched about occupational noise exposure and hearing, blood pressure, cardiovascular changes in various countries [18][19][20][21][22][23], however, similar research was seldom carried out in China and no report was found in large-scale industrial city of Chongqing. To resolve this problem in the area, we did this study.…”
Section: Discussionmentioning
confidence: 99%